2022
DOI: 10.2196/36263
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Services for Substance Use Disorders During the COVID-19 Pandemic: Longitudinal Assessment of Intensive Outpatient Programming and Data Collection Practices

Abstract: Background The onset of the COVID-19 pandemic necessitated the rapid transition of many types of substance use disorder (SUD) treatments to telehealth formats, despite limited information about what makes treatment effective in this novel format. Objective This study aims to examine the feasibility and effectiveness of virtual intensive outpatient programming (IOP) treatment for SUD in the context of a global pandemic, while considering the unique chall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…To counteract this, there has been a dramatic increase in telehealth availability, particularly in the treatment of SUDs [ 78 ]. Studies have shown virtual outpatient care for the treatment of SUD to be a feasible alternative to in-person-only programming [ 79 ]. However, access to these virtual programs can be limited by advanced age as older adults might have limited computer literacy, limited access to internet and technology, or hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…To counteract this, there has been a dramatic increase in telehealth availability, particularly in the treatment of SUDs [ 78 ]. Studies have shown virtual outpatient care for the treatment of SUD to be a feasible alternative to in-person-only programming [ 79 ]. However, access to these virtual programs can be limited by advanced age as older adults might have limited computer literacy, limited access to internet and technology, or hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the seven included publications dealt with opioid use disorder, another dealt with alcoholism, one dealt with tobacco, and the final one was on SUD. A longitudinal research conducted between January 2020 and March 2021 on 3642 patients with SUD found no significant differences in continuous abstinence, overall quality of life, financial well-being, psychological well-being, and confidence in one's ability to stay sober when treated by various health formats like in-person care only (n=957, 26.3%), hybrid, in-person and virtual care (n=541, 14.9%), and virtuosic care (n=2144, 58.9%) [15]. This study shows telepsychiatry is equally effective in the treatment and prognosis of SUD patients when compared to in-person treatment.…”
Section: Prognosis Of Sud Patients With Telepsychiatrymentioning
confidence: 98%
“…The overall studies, when combined, gave an overview that telepsychiatry/telemedicine treatment in the prognosis of addiction patients is similar to in-person treatment [15,17,[19][20][21]. In contrast, two studies have mentioned that telepsychiatry, combined with in-person treatment, produced higher retention rates and decreased premature dropouts [16,18].…”
Section: Prognosis Of Sud Patients With Telepsychiatrymentioning
confidence: 99%
“…Another meta-analysis of 20 studies representing 1418 participants found no meaningful difference between those receiving internet-based CBT to face-to-face treatment (SMD 0.05 (95% CI − 0.09–0.20)). Simultaneously, a longitudinal study following 1060 patients in intensive outpatient addiction treatment in the USA found no significant differences in delivery format ( χ 2 = 0.4, p = 0.81), overall quality of life ( F = 2.06, p = 0.13), psychological well-being ( F = 0.72, p = 0.49), financial well-being ( F = 2.30, p = 0.10), and the patient’s confidence to stay sober between patients receiving virtual outpatient programming treatment for SUD as opposed to in-person ( F = 0.21, p = 0.81) [ 32 •]. In another narrative review, 7 out of 8 included studies comparing virtual and in-person provision of addiction treatment showed that telehealth was as effective but not better than in-person treatment in terms of retention, therapeutic alliance, and substance use [ 16 ].…”
Section: Evidence On the Use Of Telepsychiatry For Mental Healthmentioning
confidence: 99%
“…As telehealth may not be suitable for all medication types for OUD patient, it is recommended that a hybrid care delivery model is developed that can manage both patient and provider needs [ 47 ]. Patients in hybrid in-person/virtual programs reported higher levels of general health than those in entirely virtual intensive outpatient programming treatment for SUD [ 32 •]. Hybrid delivery systems may offer flexibility and effectiveness in many circumstances.…”
Section: Clinical Users Of Telepsychiatrymentioning
confidence: 99%